What Drives the Global “Land Rush”? - Arezki, Rabah (Oxford University Press on behalf of the World Bank, 2017)
We review evidence regarding the size and evolution of the "land rush" in the wake of the 2007–8 boom in agricultural commodity prices, and we study the determinants of foreign land acquisition for large-scale agricultural investment. The use of data on bilateral investment relationships to estimate gravity models of transnational land-intensive investments confirms the central role of agro-ecological potential as a pull factor. However, this finding contrasts the standard literature insofar as the quality of the destination country's business climate is insignificant, and weak tenure security is associated with increased interest for investors to acquire land in the country. Policy implications are discussed.